Toxicity Syndromes, Patient-Related Clinical Indicator of Toxicity Burden Induced by Intensive Triplet Chemotherapy-Based Regimens in Gastrointestinal Cancers With Metastatic Disease - Bruera, Gemma; Ricevuto, Enrico (Frontiers in Oncology, 2020)
Background: Cancer treatments induce symptoms/signs superimposing on individual patient’s clinical status, determining heterogenous toxicity syndromes (TS). We reviewed intensive first line triplet chemotherapy-based regimens in metastatic gastro-intestinal cancers (mGI), based on FIr/FOx schedule, fluorouracil and weekly alternating irinotecan/oxaliplatin, to point out limiting TS (LTS) relevance. Methods: metastatic colo-rectal (mCRC), pancreatic ductal adenocarcinoma (mPDAC), gastric carcinoma (mGC) patients were enrolled by careful decision-making including age, performance status (PS), and comorbidity status in real life phase II studies: FIr-B/FOx adding bevacizumab (B) overall, FIr-C/FOx-C adding cetuximab (C) in KRAS/NRAS wild-type mCRC; FIr/FOx in mPDAC; FD/FOx adding docetaxel (D) in mGC. Toxicity, individual LTS, LT alone (LTS-single site, LTS-ss) or associated to other limiting/G2 toxicities (LTS-multiple sites, LTS-ms) were evaluated, compared by chi-square test. In FIr-C/FOx-C, 5-fluorouracil/irinotecan pharmacogenomic biomarkers, 5-fluorouracil degradation rate (5-FUDR), SNPs ABCB1, CYP3A4, DYPD, UGT1A1 were evaluated, related with LTS. Results: FIr-B/FOx, FIr-C/FOx-C in mCRC, FIr/FOx in mPDAC, FD/FOx in mGC, showed activity, efficacy, toxicities similar to reported triplet regimens. LTS: mCRC FIr-B/FOx 44%, LTS-ms 24%, LTS-ss 20%, in young-elderly 46%, LTS-ms significantly increased vs LTS-ss; FIr-C/FOx-C 65.5%, significantly increased LTS-ms vs LTS-ss, in young-elderly 83%; mPDAC FIr/FOx 27.5%, mostly LTS-ms, in young-elderly 38.4% all LTS-ms; mGC FD/FOx 30%, all LTS-ms, in young-elderly 25%. Reduced FUDR, SNPs CYP3A4, UGT1A1, >1 positive pharmacogenomic biomarkers were prevalent in patients with gastrointestinal LTS. Conclusions: LTS is an innovative clinical parameter of toxicity burden, differential treatment-related TS in individual patient. LTS can evaluate pharmacogenomic biomarkers predictive relevance to select mGI patients fit for intensive treatments, at risk of limiting gastrointestinal toxicity. Trial registrations: The trials were registered at Osservatorio Nazionale sulla Sperimentazione Clinica dei Medicinali (OsSC) Agenzia Italiana del Farmaco (AIFA) Numero EudraCT 2007-004946-34, and Osservatorio Nazionale sulla Sperimentazione Clinica dei Medicinali (OsSC) Agenzia Italiana del Farmaco (AIFA) Numero EudraCT 2009- 016793-32.